Effectiveness of Calf Muscle Stretching Exercise on leg Cramps among Antenatal Mothers Attending a Tertiary Care Centre Thiruvananthapuram (International Journal of Nursing Care, 2025)
Background: Leg cramps during pregnancy is a common discomfort characterized by involuntary,painful contraction of muscle groups that usually occur in the calf or small muscles of the foot but canaffect different part of the leg. The severity of the leg cramp pain is variable and each attack may takefew minutes. 1 The prevalence of leg cramps occurred among 30% to 50% of pregnant women. Legcramping means painful spasm especially in the lower extremities occurs during pregnancy andmainly occurred in the second half of pregnancy typically occurs at night and usually lasts for a fewseconds or 2 minutes. 2Materials and Methods:The objective of the present study was to assess the effectiveness of calfmuscle stretching exercise on leg cramps among antenatal mothers. The research approach adoptedfor the study was quantitative approach and the research design was quasi experimental pre-test post-test control group design. Sample size was 80 and the samples who satisfied the inclusion andexclusion criteria were selected consecutively. Informed consent was obtained from those participantswho were willing to participate in the study. The investigator collected socio demographic data,clinical data and history of leg cramps by a self- prepared semi structured questionnaire and intensityof leg cramps was assessed using numeric pain rating scale. The investigator demonstrated thestretching exercise and provided with a diary to note down the intensity, duration and frequency of legcramps and the post-test was conducted after two weeks.Results: The collected data was analyzed using SPSS version 22 and description of participants basedon socio demographic data, clinical data and history of leg cramps were analyzed using percentageand frequencies and the effectiveness of calf muscle stretching exercise on frequency and duration ofleg cramps among experimental and control group was analyzed using chi-square test and thecalculated p value was <0.05, it was concluded that calf muscle stretching exercise was effective inreducing frequency and duration of leg cramps among experimental group also the effectiveness ofcalf muscle stretching exercise on intensity of leg cramps was analyzed by independent t-test. It wasfound that the mean difference in NPRS score in the experimental was 2.03±0.66 and in the controlgroup was 0.35±1.14 and the calculated p value was <0.05.Conclusion: calf muscle stretching exercise is effective in reducing intensity of leg cramps amongantenatal mothers.
Keywords: leg cramps; stretching exercise; antenatal mothers.